Foraging habitat choice of White-tailed Tropicbirds revealed by fine-scale GPS tracking and remote sensing - Carlos D. Santos; Leila F.A.S. Campos; Márcio A. Efe (PeerJ, 2019)
Background The introduction of animal tracking technology has rapidly advanced our understanding of seabird foraging ecology. Tracking data is particularly powerful when combined with oceanographic information derived from satellite remote sensing, allowing insights into the functional mechanisms of marine ecosystems. While this framework has been used extensively over the last two decades, there are still vast ocean regions and many seabird species for which information is scarce, particularly in tropical oceans. Methods In this study we tracked the movement at high GPS recording frequency of 15 White-tailed Tropicbirds (Phaethon lepturus) during chick-rearing from a colony in Fernando de Noronha (offshore of Northeast Brazil). Flight behaviours of travelling and searching for food were derived from GPS data and examined in relation to satellite-sensed oceanographic variables (sea surface temperature, turbidity and chlorophyll-a concentration). Results White-tailed Tropicbirds showed marked preference for clear and warm sea surface waters, which are indicative of low primary productivity but are likely the best habitat for preying upon flying fish. Discussion These findings are consistent with previous studies showing that foraging habitat choices of tropical seabirds may not be driven by primary productivity, as has been widely shown for non-tropical species.